2017
DOI: 10.1016/j.ymthe.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy of Preventive and Therapeutic Vaccines Targeting the N Terminus of β-Amyloid in an Animal Model of Alzheimer’s Disease

Abstract: Previously, we reported that Alzheimer's disease (AD) epitope vaccines (EVs) composed of N-terminal b-amyloid (Ab 42 ) B cell epitope fused with universal foreign T helper (Th) epitope(s) were immunogenic, potent, and safe in different amyloid precursor protein (APP) transgenic mice with early AD-like pathology. However, developing an effective therapeutic vaccine is much more challenging, especially when a self-antigen such as Ab 42 is a target. Here, we directly compare the efficacy of anti-Ab 42 antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 83 publications
3
12
0
Order By: Relevance
“…The Aβ accumulation and accompanying neuronal loss have been corroborated in the previous studies [ 30 , 31 ]. To assess whether the reduction of Aβ accumulation can attenuate synaptic deficits, we used anti-synaptophysin antibody to detect the effect of Y-5A15 yeast vaccine on the synapses.…”
Section: Resultssupporting
confidence: 84%
“…The Aβ accumulation and accompanying neuronal loss have been corroborated in the previous studies [ 30 , 31 ]. To assess whether the reduction of Aβ accumulation can attenuate synaptic deficits, we used anti-synaptophysin antibody to detect the effect of Y-5A15 yeast vaccine on the synapses.…”
Section: Resultssupporting
confidence: 84%
“…To study how the immunization with AV-1980R/A affects cognition, PS19 mice were also tested in novel object recognition (NOR) and novel place recognition (NPR) paradigms, which rely on cortical and hippocampal function respectively, both areas strongly affected by AD pathology 4446 . This analysis demonstrated that vaccination of PS19 mice with AV-1980R/A resulted in a significant increase in the exploration of a non-familiar object as indicated by the increased discrimination index compared with mice injected with adjuvant only ( p < 0.01 ; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Novel object and novel place recognition tests were used to evaluate cognition as previously described 46,77 . All combinations of locations and objects were balanced across trials to eliminate bias.…”
Section: Methodsmentioning
confidence: 99%
“…The MultiTEP strategy provides a unique opportunity to generate high levels of antibodies in the elderly by activating not only naïve Th cells, but also pre-existing memory Th cells previously generated in response to infections and/or vaccinations with tetanus toxin, hepatitis B, and influenza, thereby overcoming immunosenescence. Indeed, the feasibility of this strategy based on pre-existing memory Th cells was previously demonstrated [10, 21, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, we demonstrated that in mice and monkeys, AV-1959 induced antibodies specific to the AEFRH epitope of Aβ 1–11 peptide incorporated in this vaccine [41]. This immunodominant B cell epitope of N-terminus of Aβ 42 [45] is widely used in preclinical and clinical studies, and data from various groups, including us, suggest that high-affinity antibodies specific to this region reduce AD-like pathology not only in mouse models of AD but also in brains of vaccinated people [18, 20, 21, 25, 44, 4651]. Immunizations with AV-1959R/A also induced therapeutically potent antibodies that significantly reduced soluble and insoluble Aβ 42 pathology in this pathologically aggressive bigenic mouse model of AD (Fig.…”
Section: Discussionmentioning
confidence: 99%